MODEL PENILAIAN RISIKO KREDIT DAN KEGAGALAN MODEL MERTON TAHUN 1974: SEBUAH TELAAH KONSEPTUAL - Wendy . (Faculty of Economic and Business Universitas STIKUBANK, 2015)
This article examines various models of credit risk assessment. The study results show that the models can be classified based on the approach adopted, namely the traditional and the structural. In its development, the structural approach by Merton model is dominating, although at the end it reaps many critics when the LTCM crisis happened in America, in the late 1998. Those critics lead to the assumptions used, which considers only the endogenous factor without having to analyze the exogenous factor. The failure of the Merton model has its own attention from the experts so that many of them are trying to polish them. Nevertheless, the results showed that each model has its own advantages and disadvantages that need a comprehensive understanding and analysis of the managers when they want to adopt one of them.Keywords: Credit risk, Merton model, firm-specific risk, and market risk.